Patterns of aggressive behavior among kindergarten children and treatment methods (Journal of the College of Basic Education, 2022)
mulakhis albhth:yueadu alsuluk aleudwaniu zahiratan eamatan bayn albashar yumarisuha al'afrad bi'asalib mukhtalifat wamutanawieat watakhudh sur fi altaebir biallafaz 'aw aleudwan albadanii , waqad yatakhidh aleudwan sur alhulak 'aw alharq 'aw al'iitlaf lamaa yuhibu albashr.walikhuturat tatbue altifl biainmat alsalukiaat waltasadiy laha wali'atfaliha wa'atfalahum wa'atfaluhum , wawajihatiha watariqat taeamuliha maeahawamin ajl tahqiq hdha alhadaf altawajuh 'iilaa eaynuh min muealamat riad al'atfal fi mumarasat altaelim waltaearuf ealaa almumarasat alhukumiat waltaearuf ealaa mawaqie alriyad , muqtarahatihin fi al'asalib alssadirat 'ahamu alnatayij alty tawasal 'iilayha albahth , hy- wujud halat min alsuluk aleudwanii ladaa edt 'anwae min 'anwae altawafur. - aiqtirah almuelamat min alturuq muealajat alsuluk aleudwanii lil'atfal minhu . alkalimat almuftahiatu: alsuluk aleudwaniu , turuq alnas